Longitudinal studies of IQ stability in children with childhood autism : literature survey - Begovac, Ivan (Array, 2009)
In this paper we present a survey of the literature dealing with IQ stability in children with childhood autism (CA) over the last ten years. Nowadays there is no clear evidence on this topic. : We used the online "PubMed" database. By inputting the following key words: (autism and IQ and child) and (stability or outcome or follow-up) we obtained a total of 78 references. Out of those 78 references, some papers were left out in line with the exclusion criteria, so this survey includes 23 papers altogether. At an individual level, single studies show a similar trend to the general results.The majority of studies state that the IQ points will remain the same. Today the generally accepted belief is that therapy should be started intensely and early. Some children with good progress may attend regular school